Social work encounters of the first kind : child protection social workers' experiences of preparing for, and meeting their clients for the first time : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Manawatu, New Zealand - Bowden, Sandra Eva (Massey University, 2019)
This research investigates the experiences of child protection social workers as they prepare to meet the client families they work with for the first time. It is important to understand the experiences of social workers in child protection as first contact with clients is a critical time and the experience lays the foundation for any ongoing relationship. The study speaks to social workers experiences on the “front line” and adds to the body of knowledge evolving in the home visiting space. The study applied a qualitative framework and employed semi-structured interviews to gather rich, descriptive data of social worker experience. The results found that child protection social workers practice in an environment constructed as a neoliberal process that positions risk and mitigating risk as sacrosanct ahead of welfare or supporting families in need. This construction pervades the first contact space and constrains a social work process. Recommendations call for the reconstruction of first contact in child protection as a critically reflexive process that is relationship focussed and accounts for structural inequalities.
Keywords: Social work with children; Family social work; Child welfare workers; New Zealand; Attitudes; 440901 Clinical social work practice